The Effect of 2025 Government Budget Efficiency Policy on Subcontractor Performance in Supporting Main Contractor Work Completion: Paspampres Headquarters Project - Enny Vebriyanti Novian; M. Zaki (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze the effect of the 2025 government budget efficiency policy on subcontractor performance in supporting the completion of main contractor work in the MAKO Paspampres Project, Central Jakarta. The research employs a mixed-methods approach within a case study framework, combining qualitative and quantitative analyses. Data were collected through interviews, observations, and questionnaires involving subcontractors, main contractors, and project managers, supported by secondary data such as project documents, government regulations, and academic literature. The results indicate that the budget efficiency policy has a positive and significant effect on subcontractor performance, with a regression coefficient of 0.591 and a significance value of less than 0.05. The policy also influences project management adjustments and affects the completion of construction work. Subcontractor performance plays a crucial role in project success, particularly in terms of time, cost, and quality. Therefore, adaptive strategies and effective coordination among stakeholders are essential to maintain project stability and ensure successful completion.